2018
DOI: 10.1111/pan.13309
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of common IV drugs with 6% hydroxyethyl starch 130/0.42 and 4% gelatin

Abstract: Most of the tested drugs did not show observable incompatibility reactions. However, some common drugs are highly incompatible with colloid infusion solutions: gelatin (cefazolin, diazepam, midazolam, phenytoin, vancomycin), hydroxyethyl starch (diazepam, midazolam, phenytoin, thiopental), and NaCl 0.9% (diazepam, ketamine (S), phenytoin, thiopental). These combinations should be avoided in clinical practice in case there are fewer intravenous lines available than needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In this study, only minor changes in OD were observed, which did not exceed the control experiments, whereas in previous studies, incompatible drug-infusion mixtures showed an increase of up to 6.91 times the initial OD. 5,6 Therefore, we conclude that no major incompatibility reactions occurred in this study.…”
Section: Turbidimetric Measurementssupporting
confidence: 48%
See 2 more Smart Citations
“…In this study, only minor changes in OD were observed, which did not exceed the control experiments, whereas in previous studies, incompatible drug-infusion mixtures showed an increase of up to 6.91 times the initial OD. 5,6 Therefore, we conclude that no major incompatibility reactions occurred in this study.…”
Section: Turbidimetric Measurementssupporting
confidence: 48%
“…However, significant changes in electrical conductivity rarely occur in compatibility testing. 5,6 In this study, slight changes were detected initially when adding glucose to Sterofundin ISO. This confirms the idea that a change of molecules in solution (glucose in this case) may change the electrical conductivity of the same solution.…”
Section: Electrical Conductivitymentioning
confidence: 66%
See 1 more Smart Citation
“…Meropenem was also tested in combination with gelatine 4% (compatible) and hydroxyethyl starch (pH change observed) as infusion solutions. 19 However, only a period of 1 h was observed in that study. In our study, incompatibility occurred after a time period of more than 1 h. Therefore, meropenem should not be mixed with both electrolyte solutions and acetaminophen.…”
Section: Laboratory Findingsmentioning
confidence: 70%
“…Heiderich et al 18 indicated meropenem as compatible with two isotonic electrolyte solutions (Sterofundin and E148G1 Paed). Meropenem was also tested in combination with gelatine 4% (compatible) and hydroxyethyl starch (pH change observed) as infusion solutions 19 . However, only a period of 1 h was observed in that study.…”
Section: Discussionmentioning
confidence: 99%